A wet- and dry-process feasible carbazole type host for highly efficient phosphorescent OLEDs. Issue 47 (18th November 2015) - Jou, Jwo-Huei; Sahoo, Snehasis; Kumar, Sudhir; Yu, Hui-Huan; Fang, Po-Hsun; Singh, Meenu; Krucaite, Gintare; Volyniuk, Dmytro; Grazulevicius, Juozas Vidas; Grigalevicius, Saulius
Abstract : A wet- and dry-process feasible host material is crucial to realize, respectively, low cost roll-to-roll fabrication of large area and high performance organic light-emitting diodes (OLEDs) with precise deposition of organic layers. Abstract : A wet- and dry-process feasible host material is crucial to realize, respectively, low cost roll-to-roll fabrication of large area and high performance organic light-emitting diodes (OLEDs) with precise deposition of organic layers. We demonstrate in this study high efficiency phosphorescent OLED devices by employing a newly synthesized carbazole based host material 1, 6-bis[3-(2-methoxy-3-pyridinyl)carbazol-9-yl]hexane (compound5 ). Moreover, two other carbazole hosts 1, 6-bis[3-(6-methoxy-3-pyridinyl)carbazol-9-yl]hexane (compound4 ) and 3, 6-di(2-methoxy-3-pyridinyl)-9-ethylcarbazole (compound6 ) are also synthesized for comparison. By doping a typical green emitter fac tris(2-phenylpyridine)iridium (Ir(ppy)3 ) in compound5, for example, the resultant wet-processed device exhibits at 100 cd m −2 a current efficiency of 27 cd A −1 and a power efficiency of 16.1 lm W −1 . The dry-processed device shows a current efficiency of 61 cd A −1 and a power efficiency of 62.8 lm W −1 . The high efficiency may be attributed to the host possessing an effective host-to-guest energy transfer, effective carrier injection balance, and the device architecture enabling excitons to generate on both the host and the guest.